STRATEGI KOMUNIKASI BADAN PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK DAN KELUARGA BERENCANA DALAM MEWUJUDKAN PROGRAM KABUPATEN LAYAK ANAK DI KABUPATEN SIAK - Eko Purnomo; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Regency/city worthy of a Child is a term first introduced by the country's Ministry of women's empowerment in 2005 through City Policy worthy of children. Due to accommodate the Government Area, later the term City worthy of Children into Kabupaten/Kota Worthy son and later shortened to KLA. In the policy described that the KLA is the effort of the Government district/municipality to speed up the implementation of the Convention on the rights of the child (CRC) from the legal framework into the definition, development and intervention Strategies, such as the policies, institutions, and programs that are worthy of a child. Defenition KLA is a district/city has a system of child rights-based development through the integration of the commitment and resources of Government, business community and thoroughly planned and sustainable policies, programs and activities for the fulfillment of the rights of the child. In the implementation of the KLA, Siak Regency also involve government agencies and local communities. This study uses qualitative methods, data collection techniques used in this researchis the interview, observation, and documentation. As for the subject of the Informants were selected using a purposive technique, which became informants in this study amounted to 9 informant i.e., Kasubag BP3AKB and 2 staff, 1, 1 Department of Health Office of education and culture, Chairman of the children's Forum Siak Regency, the facilitator Forum Child while Riau Child Ambassadors as well as 2 local community people. Data analysis techniques with the reduction of data, collecting data, presenting data, draw conclusions and evaluation by using the technique of examination of the validity of the data, namely the extension of participation and triangulation. The results of this discussion shows that the role of the institutions and the community is very important to speed up the fulfillment of the rights, obligations and the protection of children in Indonesia particularly in Siak Regency. Communities in Siak Regency strongly support and support of local government. The existence of this program, providing a positive impact on the development and growth of children at once can support creativity for children can be expected to be the next generation for growth and progress as a particularly child-friendly District Siak Regency as well as to Indonesia.Keywords: Child, Country, child protection, child-friendly Country